Self-supporting membrane negative electrode material, preparation method thereof and sodium ion battery

The self-supporting membrane negative electrode material is prepared by combining one-dimensional nanocellulose and zero-dimensional coal powder, which solves the complex and high cost of sodium ion battery preparation process and achieves efficient battery performance improvement.

CN119812204AActive Publication Date: 2025-04-11GUOKE TANMEI NEW MATERIALS (HUZHOU) CO LTD +2
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510293985.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

The preparation process of existing sodium ion batteries is complex, costly, and capacity performance and rate performance need to be improved.

Method used

One-dimensional nanocellulose and zero-dimensional coal powder are used to directly prepare the self-support film negative electrode material, avoiding the complex process in the powder preparation process, saving the use of adhesive, and improving conductivity through electroplating.

Benefits of technology

The preparation process is simplified, cost is reduced, and the specific capacity, first-time Coulomb efficiency and rate performance of sodium ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812204A_ABST
    Figure CN119812204A_ABST
Patent Text Reader

Abstract

The invention provides a self-supporting membrane negative electrode material, a preparation method thereof and a sodium ion battery, and belongs to the technical field of battery materials. The preparation method comprises the following steps: mixing pulverized coal and a one-dimensional nanocellulose solution to obtain a mixed solution; carrying out suction filtration on the mixed solution to obtain a composite film; and sequentially carrying out pre-carbonization and secondary carbonization on the composite film to obtain the self-supporting film negative electrode material. The one-dimensional nano cellulose and the zero-dimensional pulverized coal are matched with each other, the self-supporting membrane negative electrode material can be directly prepared, powder does not need to be formed, composite processes such as homogenization, coating and drying are avoided, the preparation method is simple and easy to implement, the use of a binder is saved, and the preparation cost is greatly reduced. Moreover, the one-dimensional nanocellulose formed by the process surrounds the structure of zero-dimensional pulverized coal particles, so that the wettability of an electrolyte on a negative electrode material is improved, the diffusion and migration of sodium ions are improved, and the sodium ion battery has relatively high specific capacity, initial coulombic efficiency and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a self-supporting film negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] The abundant sodium reserves give sodium-ion batteries a significant cost advantage, which is expected to reduce battery costs and improve market competitiveness. In sodium-ion batteries, conventionally prepared sodium negative electrode materials are all powder materials. After the powder materials are prepared into negative electrode materials, they still need to be homogenized, coated, dried and other processes to prepare them into negative electrode sheets. This preparation method is relatively complicated and costly, and the capacity performance and rate performance of the sodium-ion batteries prepared based on this method need to be further improved.

[0003] Therefore, how to solve the problem of complex preparation process mentioned above, save the use of binder in the process of preparing pole pieces with powder negative electrode materials, significantly reduce the preparation cost, and further improve the capacity performance and rate performance of sodium ion batteries, is the focus of current research. Summary of the invention

[0004] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a self-supporting film negative electrode material and a preparation method thereof and a sodium ion battery. The present invention utilizes one-dimensional nanocellulose and zero-dimensional coal powder to cooperate with each other, and can directly prepare a self-supporting film negative electrode material without forming a powder, avoiding the composite processes such as slurrying, coating, and drying. It is simple and easy to operate, saves the use of binders, and greatly reduces the preparation cost. In addition, the structure of one-dimensional nanocellulose surrounding zero-dimensional coal powder particles formed by the process helps to improve the wettability of the electrolyte to the negative electrode material, improve the diffusion and migration of sodium ions, and make the sodium ion battery have a higher specific capacity, first coulomb efficiency and rate performance.

[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a self-supporting film negative electrode material, the preparation method comprising the following steps: The coal powder and the one-dimensional nanocellulose solution are mixed to obtain a mixed solution.

[0006] The mixed solution is filtered to obtain a composite film.

[0007] The composite film is subjected to pre-carbonization and secondary carbonization in sequence to obtain the self-supporting film negative electrode material.

[0008] The present invention utilizes one-dimensional nanocellulose and zero-dimensional coal powder to cooperate with each other, and can directly prepare a self-supporting film negative electrode material without forming a powder, avoiding the composite processes such as slurrying, coating, and drying, which is simple and easy to implement, saves the use of binders, and greatly reduces the preparation cost. In addition, the structure of one-dimensional nanocellulose surrounding zero-dimensional coal powder particles formed by the process helps to improve the wettability of the electrolyte to the negative electrode material, improve the diffusion and migration of sodium ions, and make the sodium ion battery have a higher specific capacity, first coulomb efficiency and rate performance.

[0009] Preferably, the coal powder is ultrafine coal powder.

[0010] Preferably, the particle size D50 of the ultrafine coal powder is 0.2-2 μm, for example, it can be 0.2 μm, 0.5 μm, 1 μm, 1.5 μm or 2 μm.

[0011] Preferably, the type of coal powder includes any one of anthracite, lean coal, lean coal, coking coal, fat coal, gas coal, slightly sticky coal, non-sticky coal, long flame coal or lignite, or a combination of at least two of them, preferably long flame coal.

[0012] Preferably, the concentration of the one-dimensional nanocellulose solution is 2-20 mg / mL, for example, it can be 2 mg / mL, 4 mg / mL, 6 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL, 14 mg / mL, 16 mg / mL, 18 mg / mL or 20 mg / mL.

[0013] Preferably, in the one-dimensional nanocellulose solution, the aspect ratio of the one-dimensional nanocellulose is (100-1000):1, for example, it can be 100:1, 200:1, 300:1, 400:1, 500:1, 600:1, 700:1, 800:1, 900:1 or 1000:1, etc.

[0014] In the present invention, one-dimensional nanocellulose with a suitable aspect ratio helps the nanocelluloses to overlap each other to form a two-dimensional planar porous network structure, and has a certain function of strengthening zero-dimensional coal powder particles.

[0015] Preferably, the weight ratio of the coal powder to the one-dimensional nanocellulose solution is (1-10):100, for example, it can be 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100 or 10:100, etc., preferably (3-7):100.

[0016] In the present invention, the pulverized coal and the one-dimensional nanocellulose solution in an appropriate weight ratio cooperate with each other, which is conducive to forming a cage-like structure in which the one-dimensional nanocellulose surrounds the zero-dimensional super-pulverized coal particles.

[0017] Preferably, the mixing process is accompanied by stirring.

[0018] Preferably, the stirring speed is 100-500 rpm, for example, it can be 100 rpm, 200 rpm, 300 rpm, 400 rpm or 500 rpm.

[0019] Preferably, the stirring time is 1-5 h, for example, 1 h, 2 h, 3 h, 4 h or 5 h.

[0020] Preferably, the filtration method is vacuum filtration.

[0021] Preferably, the vacuum degree of the vacuum filtration is 10-100Pa, for example, it can be 10Pa, 20Pa, 30Pa, 40Pa, 50Pa, 60Pa, 70Pa, 80Pa, 90Pa or 100Pa, etc., preferably 20-60Pa.

[0022] Preferably, electroplating is performed between the pre-carbonization and the secondary carbonization, and the specific steps of the electroplating include: The pre-carbonized composite film is placed in an electroplating solution for electroplating, thereby depositing a metal conductive layer on the surface of the composite film.

[0023] In the present invention, the surface of the composite film is modified by electroplating, which can solve the problem of poor conductivity of conventional hard carbon negative electrode materials, effectively improve the transmission characteristics of electrons, and improve the rate properties of sodium ion batteries.

[0024] Preferably, the electroplating solution includes an aluminum-based solution and / or a copper-based solution, for example, a copper sulfate solution, a cuprous hydride solution or an aluminum sulfate solution.

[0025] Preferably, the electroplating time is 2-60 min, for example, it can be 2 min, 5 min, 10 min, 20 min, 30 min, 40 min, 50 min or 60 min, etc., preferably 2-20 min.

[0026] In the present invention, a suitable electroplating time can obtain a metal conductive layer of suitable thickness. If the time is too long, the thickness of the metal conductive layer will be too thick, which will seriously affect the performance of the negative electrode material. If the time is too short, the purpose of improving the conductivity of the negative electrode material cannot be achieved.

[0027] Preferably, the working temperature of the electroplating is 40-60°C, for example, it can be 40°C, 45°C, 50°C, 55°C or 60°C.

[0028] Preferably, the thickness of the metal conductive layer is 0.1-5 μm, for example, 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc.

[0029] Preferably, the pre-carbonization temperature is 1200-1400°C, for example, 1200°C, 1300°C or 1400°C.

[0030] In the present invention, the purpose of pre-carbonization is to transform the microcrystalline structure inside the self-supporting film formed by coal powder and nanofibers, forming a "house of cards" microcrystalline structure that is easy to store sodium.

[0031] Preferably, the pre-carbonization time is 1-5 h, for example, 1 h, 2 h, 3 h, 4 h or 5 h.

[0032] Preferably, the heating rate of the pre-carbonization is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0033] In the present invention, if the heating rate of the pre-carbonization is too fast, it will cause the rapid shrinkage of the composite film and generate a large number of cracks, resulting in the inability to form the self-supporting film negative electrode material and making it unusable in the subsequent battery assembly process.

[0034] Preferably, the temperature of the secondary carbonization is 600-800°C, for example, 600°C, 700°C or 800°C.

[0035] In the present invention, the purpose of secondary carbonization is to liquefy the surface electroplating layer, increase the bonding force between the material surface and the metal layer, and at the same time allow the liquid metal to penetrate into the interior of the membrane to fill part of the macroporous structure.

[0036] Preferably, the secondary carbonization time is 0.5-3 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0037] Preferably, the heating rate of the secondary carbonization is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0038] In the present invention, if the heating rate of the secondary carbonization is too fast, it will cause rapid shrinkage of the composite film, generate a large number of cracks, and cause misalignment between the surface metal plating layer and the internal film carbon layer, and in severe cases cause the dissociation of the metal plating layer.

[0039] Preferably, the preparation method comprises the following steps: (1) The raw coal is coarsely crushed to a particle size D50 of 100-200 μm (for example, 100 μm, 150 μm or 200 μm, etc.), and then finely ground to a particle size D50 of 0.2-2 μm to obtain ultrafine coal powder.

[0040] (2) Adding the ultrafine coal powder into a one-dimensional nanocellulose solution with a concentration of 2-20 mg / mL, and stirring the mixture at a rotation speed of 100-500 rpm for 1-5 hours to obtain a mixed solution.

[0041] The weight ratio of the ultrafine coal powder to the one-dimensional nanocellulose solution is (1-10):100; and in the one-dimensional nanocellulose solution, the aspect ratio of the one-dimensional nanocellulose is (100-1000):1.

[0042] (3) The mixed solution is vacuum filtered at a vacuum degree of 10-100 Pa for a filtration time of 0.5-2 h to obtain a composite film.

[0043] (4) fixing the composite film with a graphite plate fixture, and then pre-carbonizing the composite film in a protective atmosphere (such as a nitrogen atmosphere or an argon atmosphere) to obtain a pre-carbonized composite film; The pre-carbonization temperature is 1200-1400°C, the heating rate is 1-5°C / min, and the time is 1-5h.

[0044] (5) Placing the pre-carbonized composite film in an electroplating solution for electroplating, thereby depositing a metal conductive layer on the surface of the composite film to obtain an electroplated composite film.

[0045] The electroplating solution includes an aluminum-based solution and / or a copper-based solution, the electroplating time is 2-60 minutes, the electroplating working temperature is 40-60° C., and the thickness of the metal conductive layer is 0.1-5 μm.

[0046] (6) Fixing the electroplated composite film with a graphite plate fixture, and then performing secondary carbonization on the electroplated composite film in an inert atmosphere (such as a nitrogen atmosphere or an argon atmosphere) to obtain a self-supporting film negative electrode material.

[0047] The secondary carbonization temperature is 600-800°C, the heating rate is 1-5°C / min, and the time is 0.5-3h.

[0048] It should be noted that the purpose of using a graphite plate fixture to fix and press the composite film is to prevent the composite film from expanding and breaking at high temperatures.

[0049] In a second aspect, the present invention provides a self-supporting film negative electrode material, wherein the self-supporting film negative electrode material is prepared by the preparation method described in the first aspect.

[0050] In a third aspect, the present invention provides a sodium ion battery, wherein the negative electrode of the sodium ion battery comprises the self-supporting film negative electrode material as described in the second aspect.

[0051] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0052] Compared with the prior art, the present invention has the following beneficial effects: The present invention utilizes one-dimensional nanocellulose and zero-dimensional coal powder to cooperate with each other, and can directly prepare a self-supporting film negative electrode material without forming a powder, avoiding the composite processes such as homogenization, coating, and drying, which is simple and easy to operate, saves the use of binders, and greatly reduces the preparation cost. In addition, the structure of one-dimensional nanocellulose surrounding zero-dimensional coal powder particles formed by the process helps to improve the wettability of the electrolyte to the negative electrode material, improve the diffusion and migration of sodium ions, and make the sodium ion battery have a higher specific capacity (≥280mAh / g), first coulomb efficiency (≥88%) and rate performance (5C / 1C≥90%). BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a SEM image of the self-supporting film negative electrode material provided in Example 1 of the present invention.

[0054] Figure 2 The figure is a capacity performance diagram of a button-type sodium ion battery made from the self-supporting film negative electrode material provided in Example 1 of the present invention at different rates. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0056] Example 1 This embodiment provides a method for preparing a self-supporting film negative electrode material, the preparation method comprising the following steps: (1) The raw coal is coarsely crushed to a particle size D50 of 150 μm, and then finely ground to a particle size D50 of 1 μm to obtain ultrafine coal powder.

[0057] (2) Adding the ultrafine coal powder into a one-dimensional nanocellulose solution with a concentration of 2 mg / mL, and stirring the mixture at a rotation speed of 300 rpm for 3 hours to obtain a mixed solution.

[0058] Among them, the weight ratio of ultrafine coal powder to one-dimensional nanocellulose solution is 5:100; in the one-dimensional nanocellulose solution, the aspect ratio of the one-dimensional nanocellulose is 500:1.

[0059] (3) The mixed solution is vacuum filtered at a vacuum degree of 50 Pa for 1 h to obtain a composite film.

[0060] (4) Fixing the composite film with a graphite plate fixture, and then pre-carbonizing the composite film in a nitrogen atmosphere to obtain a pre-carbonized composite film.

[0061] Among them, the pre-carbonization temperature is 1300°C, the heating rate is 3°C / min, and the time is 3h.

[0062] (5) Placing the pre-carbonized composite film in an electroplating solution for electroplating, thereby depositing a metal conductive layer on the surface of the composite film to obtain an electroplated composite film.

[0063] The electroplating solution is a copper sulfate solution, the electroplating time is 2 minutes, the electroplating working temperature is 40° C., and the thickness of the metal conductive layer is 0.1 μm.

[0064] (6) Fixing the electroplated composite film with a graphite plate fixture, and then performing secondary carbonization on the electroplated composite film in a nitrogen atmosphere to obtain a self-supporting film negative electrode material.

[0065] The secondary carbonization temperature is 700°C, the heating rate is 3°C / min, and the time is 1.5h.

[0066] Figure 1 The SEM image of a self-supporting film negative electrode material provided in this embodiment is shown. It can be seen from the image that the surface of the self-supporting film presents many one-dimensional nanocellulose structures.

[0067] Figure 2 The capacity performance diagram of a button-type sodium ion battery made based on the self-supporting film negative electrode material provided in this embodiment at different rates is shown. It can be seen from the figure that the button-type sodium ion battery exhibits excellent rate performance and capacity performance.

[0068] Example 2 This embodiment provides a method for preparing a self-supporting film negative electrode material, the preparation method comprising the following steps: (1) The raw coal is coarsely crushed to a particle size D50 of 100 μm, and then finely ground to a particle size D50 of 0.2 μm to obtain ultrafine coal powder.

[0069] (2) Adding the ultrafine coal powder into a one-dimensional nanocellulose solution with a concentration of 10 mg / mL, and stirring the mixture at a rotation speed of 100 rpm for 5 hours to obtain a mixed solution.

[0070] Among them, the weight ratio of ultrafine coal powder to one-dimensional nanocellulose solution is 1:100; in the one-dimensional nanocellulose solution, the aspect ratio of the one-dimensional nanocellulose is 1000:1.

[0071] (3) The mixed solution is vacuum filtered at a vacuum degree of 10 Pa for 0.5 h to obtain a composite film.

[0072] (4) Fixing the composite film with a graphite plate fixture, and then pre-carbonizing the composite film in a nitrogen atmosphere to obtain a pre-carbonized composite film.

[0073] Among them, the pre-carbonization temperature is 1200℃, the heating rate is 1℃ / min, and the time is 5h.

[0074] (5) Placing the pre-carbonized composite film in an electroplating solution for electroplating, thereby depositing a metal conductive layer on the surface of the composite film to obtain an electroplated composite film.

[0075] The electroplating solution includes cuprous hydride solution, the electroplating time is 10 minutes, the electroplating working temperature is 45° C., and the thickness of the metal conductive layer is 0.5 μm.

[0076] (6) Fixing the electroplated composite film with a graphite plate fixture, and then performing secondary carbonization on the electroplated composite film in a nitrogen atmosphere to obtain a self-supporting film negative electrode material.

[0077] Wherein, the temperature of the secondary carbonization is 600°C, the heating rate is 1°C / min, and the time is 3h.

[0078] Example 3 This embodiment provides a method for preparing a self-supporting film negative electrode material, the preparation method comprising the following steps: (1) The raw coal is coarsely crushed to a particle size D50 of 200 μm, and then finely ground to a particle size D50 of 2 μm to obtain ultrafine coal powder.

[0079] (2) Adding the ultrafine coal powder into a one-dimensional nanocellulose solution with a concentration of 20 mg / mL, and stirring the mixture at a rotation speed of 500 rpm for 1 hour to obtain a mixed solution.

[0080] The weight ratio of the ultrafine coal powder to the one-dimensional nanocellulose solution is 10:100; and in the one-dimensional nanocellulose solution, the aspect ratio of the one-dimensional nanocellulose is 100:1.

[0081] (3) The mixed solution is vacuum filtered at a vacuum degree of 100 Pa for 2 h to obtain a composite film.

[0082] (4) Fixing the composite film with a graphite plate fixture, and then pre-carbonizing the composite film in a nitrogen atmosphere to obtain a pre-carbonized composite film.

[0083] Among them, the pre-carbonization temperature is 1400°C, the heating rate is 5°C / min, and the time is 1h.

[0084] (5) Placing the pre-carbonized composite film in an electroplating solution for electroplating, thereby depositing a metal conductive layer on the surface of the composite film to obtain an electroplated composite film.

[0085] The electroplating solution includes an aluminum sulfate solution, the electroplating time is 60 minutes, the electroplating working temperature is 60° C., and the thickness of the metal conductive layer is 4 μm.

[0086] (6) Fixing the electroplated composite film with a graphite plate fixture, and then performing secondary carbonization on the electroplated composite film in a nitrogen atmosphere to obtain a self-supporting film negative electrode material.

[0087] Wherein, the temperature of the secondary carbonization is 800°C, the heating rate is 5°C / min, and the time is 0.5h.

[0088] Example 4 The difference between this embodiment and embodiment 1 is that the weight ratio of the ultrafine coal powder to the one-dimensional nanocellulose solution is 0.5:100.

[0089] The rest of the preparation methods and parameters were the same as those in Example 1.

[0090] Example 5 The difference between this embodiment and embodiment 1 is that the weight ratio of the ultrafine coal powder to the one-dimensional nanocellulose solution is 12:100.

[0091] The rest of the preparation methods and parameters were the same as those in Example 1.

[0092] Example 6 The difference between this embodiment and embodiment 1 is that the vacuum degree of vacuum filtration is 200Pa.

[0093] The rest of the preparation methods and parameters were the same as those in Example 1.

[0094] Example 7 The difference between this embodiment and embodiment 1 is that the pre-carbonization temperature is 1100°C.

[0095] The rest of the preparation methods and parameters were the same as those in Example 1.

[0096] Example 8 The difference between this embodiment and embodiment 1 is that the pre-carbonization temperature is 1500°C.

[0097] The rest of the preparation methods and parameters were the same as those in Example 1.

[0098] Example 9 The difference between this embodiment and embodiment 1 is that the heating rate of pre-carbonization is 8° C. / min.

[0099] The rest of the preparation methods and parameters were the same as those in Example 1.

[0100] Example 10 The difference between this embodiment and embodiment 1 is that step (5) is not performed.

[0101] The rest of the preparation methods and parameters were the same as those in Example 1.

[0102] Embodiment 11 The difference between this embodiment and embodiment 1 is that the temperature of the secondary carbonization is 500°C.

[0103] The rest of the preparation methods and parameters were the same as those in Example 1.

[0104] Example 12 The difference between this embodiment and embodiment 1 is that the temperature of the secondary carbonization is 1000°C.

[0105] The rest of the preparation methods and parameters were the same as those in Example 1.

[0106] Comparative Example 1 This comparative example provides a method for preparing a self-supporting soft / hard carbon film negative electrode material, comprising the following steps: (1) Dissolve 10 g of cellulose nanofibers in 100 mL of a mixed solvent system (water / isopropanol volume ratio = 5:95) and stir evenly; add 2 g of ammonium dihydrogen phosphate to the above solution, perform vacuum impregnation and interface self-assembly at room temperature, and dry at -20 °C for 12 h to obtain an impregnated nanocellulose film; (2) The impregnated nanocellulose film was spread on a graphite fixture and subjected to hot pressing at 150°C for 15 h in an argon atmosphere to obtain a cross-linked nanocellulose film; (3) Asphalt with a softening point of 200°C and a particle size of 18 μm was selected as a soft carbon source, and n-hexane was added to the asphalt, with a mass ratio of n-hexane to asphalt being 1:1; then the cross-linked nanocellulose film was spread on the prepreg asphalt solution, and vacuum filtered to obtain a nanocellulose / asphalt-based composite film; (4) The nanocellulose / asphalt-based composite film is placed in a graphite plate fixture and then placed in a tubular furnace for hot pressing carbonization treatment under argon protection. The carbonization temperature is 1600°C, the heating rate is 10°C / min, and the carbonization time is 0.5h to obtain a self-supporting soft / hard carbon film negative electrode material.

[0107] Performance Testing The negative electrode materials provided in the above embodiments and comparative examples were directly used as the negative electrode, metallic sodium was used as the counter electrode, a 1 mol / L carbonate electrolyte (the solute was NaPF6, and the solvent included ethylene carbonate and diethyl carbonate in a volume ratio of 1:1) was used as the electrolyte, and the diaphragm was a polyethylene diaphragm. A button-type sodium ion battery was assembled, and the specific capacity, first coulombic efficiency and rate performance of the button-type sodium ion battery were tested.

[0108] The test conditions for specific capacity and first coulombic efficiency include: voltage range 0-2V, current density 30mA·g -1 The charge and discharge tests were carried out under the following conditions to obtain the reversible capacity and initial efficiency. The test conditions for rate performance include: voltage range 0-2V, the assembled button cell was charged and discharged at a rate of 1C (i.e., a current density of 30mA·g -1 ) for three cycles, and then the battery was charged and discharged at a rate of 5C (i.e., a current density of 150 mA g -1 ) for three cycles, and the reversible capacity at 5C was divided by the reversible capacity at 1C to obtain the negative electrode rate properties of the self-supporting film negative electrode material.

[0109] The test results are shown in Table 1.

[0110] Table 1

[0111] analyze: The present invention utilizes one-dimensional nanocellulose and zero-dimensional coal powder to cooperate with each other, and can directly prepare a self-supporting film negative electrode material without forming a powder, avoiding the composite processes such as slurrying, coating, and drying, which is simple and easy to implement, saves the use of binders, and greatly reduces the preparation cost. In addition, the structure of one-dimensional nanocellulose surrounding zero-dimensional coal powder particles formed by the process helps to improve the wettability of the electrolyte to the negative electrode material, improve the diffusion and migration of sodium ions, and make the sodium ion battery have a higher specific capacity, first coulomb efficiency and rate performance.

[0112] It can be seen from Example 1 and Examples 4-5 that if the weight ratio of ultrafine coal powder and one-dimensional nanocellulose solution is too small, that is, the amount of ultrafine coal powder used is small, then there are too many one-dimensional nanofibers in the self-supporting membrane, and the cage structure formed is small, which is not conducive to the performance of the rate properties of the membrane negative electrode material; if the weight ratio of ultrafine coal powder and one-dimensional nanocellulose solution is too large, that is, the amount of ultrafine coal powder used is large, it is not conducive to the formation of a self-supporting membrane. Excessive coal particles cause the membrane surface to have an uneven nature, and the particles attached to the surface are easy to fall off. At the same time, the increase in ultrafine coal powder also reduces the capacity properties of the membrane negative electrode material.

[0113] It can be seen from Examples 1 and 6 that if the vacuum degree of vacuum filtration is too high, it is not conducive to the assembly of the self-supporting membrane. Under a large vacuum degree, the binding force between the one-dimensional nanocellulose and the ultrafine coal powder is insufficient, and the membrane itself is prone to dissociation during the later carbonization process.

[0114] It can be seen from Example 1 and Examples 7-8 that if the pre-carbonization temperature is too low, it will be detrimental to the formation of a microcrystalline structure in the membrane negative electrode material, and will cause defects and functional groups on the surface of the membrane negative electrode material to be unable to be repaired, affecting the primary properties of the negative electrode material; if the pre-carbonization temperature is too high, the interlayer spacing of the microcrystalline structure of the membrane negative electrode material will be small, making it difficult for sodium ions to be transported.

[0115] It can be seen from Example 1 and Example 9 that if the heating rate of pre-carbonization is too high, the film may easily crack due to the effect of internal stress.

[0116] It can be seen from Examples 1 and 10 that if step (5) is not performed, that is, if the metal conductive layer is not deposited, the conductivity of the membrane surface is affected, which in turn affects the transmission of electrons in the membrane negative electrode material, resulting in a decrease in the rate properties of the negative electrode material.

[0117] It can be seen from Example 1 and Examples 11-12 that if the temperature of the secondary carbonization is too low, the surface electroplating layer cannot be micro-liquefied at high temperature, and the bonding force between the membrane negative electrode material and the electroplating layer cannot be enhanced, thereby affecting the electron transmission properties; if the temperature of the secondary carbonization is too high, the surface electroplating coating undergoes high-temperature volatilization and does not play a role in increasing conductivity.

[0118] It can be seen from Example 1 and Comparative Example 1 that although the preparation method adopted in the prior art can realize the preparation of high-capacity membrane negative electrode materials, the present application can improve the internal crystallite and pore structure of the membrane negative electrode by combining one-dimensional materials and zero-dimensional materials, while assisting the electroplating process to increase the conductivity of the material, thereby improving the rate properties of the material.

[0119] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a self-supporting film negative electrode material, characterized in that: The preparation method comprises the following steps: mixing the coal powder and the one-dimensional nanocellulose solution to obtain a mixed solution; The mixed solution is filtered to obtain a composite film; The composite film is subjected to pre-carbonization and secondary carbonization in sequence to obtain the self-supporting film negative electrode material.

2. The preparation method according to claim 1, characterized in that: The coal powder is ultrafine coal powder; And / or, the particle size D50 of the ultrafine coal powder is 0.2-2 μm; And / or, the type of the coal powder includes any one of anthracite, lean coal, lean coal, coking coal, fat coal, gas coal, slightly sticky coal, non-sticky coal, long flame coal or lignite, or a combination of at least two of them.

3. The preparation method according to claim 1, characterized in that: The concentration of the one-dimensional nanocellulose solution is 2-20 mg / mL; And / or, in the one-dimensional nanocellulose solution, the aspect ratio of the one-dimensional nanocellulose is (100-1000):1; And / or, the weight ratio of the coal powder to the one-dimensional nanocellulose solution is (1-10):

100.

4. The preparation method according to claim 1, characterized in that: The mixing process is accompanied by stirring; wherein the stirring speed is 100-500 rpm; and the stirring time is 1-5 hours; And / or, the filtration method is vacuum filtration; wherein the vacuum degree of the vacuum filtration is 10-100Pa.

5. The preparation method according to claim 1, characterized in that: Between the pre-carbonization and the secondary carbonization, electroplating is also performed, and the specific steps of the electroplating include: placing the pre-carbonized composite film in an electroplating solution for electroplating, thereby depositing a metal conductive layer on the surface of the composite film; And / or, the electroplating solution includes an aluminum-based solution and / or a copper-based solution; And / or, the electroplating time is 2-60min; And / or, the electroplating operating temperature is 40-60°C; And / or, the thickness of the metal conductive layer is 0.1-5 μm.

6. The preparation method according to claim 1, characterized in that: The pre-carbonization temperature is 1200-1400°C; And / or, the pre-carbonization time is 1-5h; And / or, the heating rate of the pre-carbonization is 1-5°C / min.

7. The preparation method according to claim 1, characterized in that: The temperature of the secondary carbonization is 600-800°C; And / or, the secondary carbonization time is 0.5-3h; And / or, the heating rate of the secondary carbonization is 1-5°C / min.

8. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) The raw coal is coarsely crushed to a particle size D50 of 100-200 μm, and then finely ground to a particle size D50 of 0.2-2 μm to obtain ultrafine coal powder; (2) adding the ultrafine coal powder to a one-dimensional nanocellulose solution having a concentration of 2-20 mg / mL, and stirring and mixing at a rotation speed of 100-500 rpm for 1-5 hours to obtain a mixed solution; The weight ratio of the ultrafine coal powder to the one-dimensional nanocellulose solution is (1-10):100; the aspect ratio of the one-dimensional nanocellulose in the one-dimensional nanocellulose solution is (100-1000):1; (3) vacuum filtering the mixed solution at a vacuum degree of 10-100 Pa for a filtration time of 0.5-2 h to obtain a composite film; (4) fixing the composite film with a graphite plate fixture, and then pre-carbonizing the composite film in a protective atmosphere to obtain a pre-carbonized composite film; The pre-carbonization temperature is 1200-1400°C, the heating rate is 1-5°C / min, and the time is 1-5h; (5) placing the pre-carbonized composite film in an electroplating solution for electroplating, thereby depositing a metal conductive layer on the surface of the composite film to obtain an electroplated composite film; The electroplating solution includes an aluminum-based solution and / or a copper-based solution, the electroplating time is 2-60 minutes, the electroplating working temperature is 40-60° C., and the thickness of the metal conductive layer is 0.1-5 μm; (6) Fixing the electroplated composite film with a graphite plate fixture, and performing secondary carbonization on the electroplated composite film in an inert atmosphere to obtain a self-supporting film negative electrode material; The secondary carbonization temperature is 600-800°C, the heating rate is 1-5°C / min, and the time is 0.5-3h.

9. A self-supporting film negative electrode material, characterized in that: The self-supporting film negative electrode material is prepared by the preparation method according to any one of claims 1 to 8.

10. A sodium ion battery, characterized in that: The negative electrode of the sodium ion battery comprises the self-supporting film negative electrode material as claimed in claim 9.

Citation Information

Patent Citations

  • Sodion secondary battery negative electrode material and preparing method and application thereof

    CN105185997A

  • Composite material negative electrode, battery and preparation method thereof

    CN110690420A

  • Metal electroplating composite film and preparation method thereof

    CN114351217A

  • Preparation method of high-performance foamy carbon electrode material applied to liquid flow energy storage battery

    CN114824297A

  • Self-supporting soft / hard carbon membrane for negative electrode of sodium ion battery as well as preparation and application of self-supporting soft / hard carbon membrane

    CN115275190A